Fracture mechanics based joint capacity prediction of glued-in rods with beech laminated veneer lumber. Issue 5 (1st June 2019) - Myslicki, S.; Vallée, T.; Bletz-Mühldorfer, O.; Diehl, F.; Lavarec, L. C.; Créac'Hcadec, R.
ABSTRACT: Glued-in rods (GiR) represent a very successful type of adhesively bonded joints in timber engineering. Despite their apparent geometrical simplicity, their dimensioning still challenges practitioners. A major source of mechanical complexity resides in the orthotropic nature of the wood, or engineered wood products, as laminated veneer lumber (LVL). This paper presents a relatively simple design approach based upon fracture mechanics (FM) and associated double-cantilever beam (DCB) tests that complemented tensile tests for material characterisation. In comparison with the state-of-the-art related to FM in timber engineering, the paper presents a practitioner oriented approach of a yet complex set of GiR geometries involving beech LVL (M16-8.8 threaded rods embedded in cross sections of 120 × 120 mm 2 and embedment lengths of 96mm, 128mm and 160mm). The developed numerical model resulted in a good description of the load-displacement of a series of full scale, including very good estimates of their load capacities. Additionally, it allowed for significant insights regarding the complicated relationship between geometry, orthotropy, strength of the component and failure of the GiR, as for examples the complex fracture process, and the importance of transverse tensile stresses, which play a preponderant role, equal in importance to shear stresses.